A report of a pedigree with compound heterozygous mutations in the SLC22A5 gene - Zhou, Yunguo; Liu, Yucai; Shen, Yang; Xu, Fang; Xu, Fei; Huang, Hui; Duan, Junkai (Frontiers in Pediatrics, 2023)
Introduction To investigate the clinical characteristics and disease outcomes of a pedigree with compound heterozygous mutations in the SLC22A5 gene. Methods Serum acylcarnitine profiles of patients were analyzed using tandem mass spectrometry. DNA samples isolated from patients and their first-degree relatives were subjected to high-throughput sequencing, and mutations were validated using Sanger sequencing. Results The proband, a 4-month-old girl, presented with seizure episodes and mild cardiac hypertrophy and was diagnosed with primary carnitine deficiency (PCD), with carnitine levels of 5.165 mol/L. Her brother, a 6-year-and 4-month-old boy, was also diagnosed with PCD with serum-free carnitine levels of 1.014 mol/L (reference values 10–60 mol/L). Compound heterozygous mutations (c.760C > T [p.R254X] and c.825G > A [p.W275X]) were detected in the SLC22A5 gene in both patients and were inherited from the mother and father, respectively. Oral L-carnitine significantly improved or resolved the clinical symptoms. Conclusion Children with compound mutations in SLC22A5 may present different clinical manifestations, particularly at different ages. Early clinical manifestations have a greater impact on the organs and may cause irreversible damage. PCD can cause epilepsy and dilated cardiomyopathy. Tandem mass spectrometry and high-throughput sequencing are recommended to confirm the diagnosis. Early L-carnitine supplementation can improve symptoms and reverse organ damage in some children. Tandem mass spectrometry should be used to screen for newborns with a family history of PCD.